A study into linguistic features of expressions denoting optimism in english and vietnamese economic news - Dư Trần Thiện Vi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This is a study on the syntactic, semantic and pragmatic features of the expressions denoting optimism in English and Vietnamese economic news and making comparision to find out the similarities and differences of these features between two languages. To reach the goal, the data used for examination and analysis were taken from various linguistic materials such as dictionaries, English newspapers and internet included. 400 samples were collected from popular online newspapers such as CNN, BBC in English and Vneconomy in Vietnamese. Lexically, words and phrases denoting development were found to be typical expressions employed in both language of which the English economic news were more diversified than those in Vietnamese. Syntactically, verb phrases, noun phrases, adjective phrases, preposition phrases and advevb phrases were prominent features which were thoroughly analyzed and compared. This research is also intended to draw out some implications in teaching, learning and translating. Any unanswered questions in this study require further researches due to the limited scope of the research. Hopefully, the result of the study can be somewhat beneficial for teaching and learning English. Also, this study may be useful for economic journalism students in writing news. It may help entrepreneurs, teacher and students to draw up and understand more economic news. The findings lay the foundations of implications for teaching and learning to achieve better communicative competence.